Safety and security of cultural heritage in zones of war or instability - Romiti, Beatrice; Folliero, Antonello (NATO science for peace and security series. Human and societal dynamics, 2021)
A nation's cultural heritage represents its past, its present and its path to the future, but for many years, the cultural heritage in or adjacent to war and conflict zones has been subject to continual assault, both deliberate and unintended. This book presents papers delivered at the NATO Advanced Research Workshop entitled "Cultural heritage's safety and security in zones of war or instability", hosted online by the University of Rome from 25 to 27 November 2020. NATO has always been a leading player in the protection of cultural property (CPP) in the areas in which it intervenes, indeed, the protection of cultural property and common heritage is part of NATO's core values. In addition to this, the illicit trade in antiquities and archaeological finds represents another danger to cultural heritage and can help to finance the terrorist groups that manage to seize these assets. The workshop aimed to explore ways to protect and safeguard cultural heritage in war zones or from terrorist attacks, and a group of international experts were invited to contribute presentations on selected topics of direct relevance to the processes in NATO with regard to CPP. Topics included: the experiences of international institutions; conservation and restoration; and countermeasures, technologies and examples of successful interventions. The book raises awareness of the importance of safeguarding cultural heritage and sets out ways of tackling the problem. It will be of interest to all those working in the field of protecting cultural heritage in unstable areas.